DNDFs:a more efficient way to intervene in FX markets? - Márcio Garcia; Tony Volpon (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2014)
We analyze the unique intervention strategy of the BCB using DNDFs (Domestic-Non-Deliverable Forwards): currency forwards that settle in domestic currency. We show the mechanisms through which DNDFs provide efficient hedging instruments for economic agents in times of reduced capital inflows and FX volatility, and how the use of DNDFs provide incentives for commercial banks to bring dollar to Brazil and so help finance the current account deficit. We discuss the limits to this strategy, which will work insofar as economic agents believe they can go from DNDFs to spot USD, i.e., that convertibility risk is negligible. We also have described how the strategy creates increasing positions within the commercial banking system (basis and roll over risks), generating possible threats to financial stability. The gain of not having to sell down hard currency reserves in the present strategy should be weighed against these risks. We conclude that the BCB's strategy does provide an alternative intervention strategy, which is made possible only due to specific features of the Brazilian financial markets and its legislation. It is not clear that other emerging markets would profit from adopting such intervention strategy in FX markets
Keywords: F31; F32; F36; F65; 330; Sterilized FX Interventions; Capital Flows; Macroprudential Policies; NDFs; Exchange Rate; Brazil